American Illuminations : Urban Lighting, 1800-1920. - Nye, David E. (MIT Press Ser., 2019)
How Americans adapted European royal illuminations for patriotic celebrations, spectacular expositions, and intensely bright commercial lighting to create the world's most dazzling and glamorous cities.